Deep eutectic solvents as smart cosubstrate in alcohol dehydrogenase-catalyzed reductions - Chanquia, Santiago Nahuel (2020)
Alcohol dehydrogenase (ADH) catalyzed reductions in deep eutectic solvents (DESs) may become efficient and sustainable alternatives to afford alcohols. This paper successfully explores the ADH-catalyzed reduction of ketones and aldehydes in a DES composed of choline chloride and 1,4-butanediol, in combination with buffer (Tris-HCl, 20% v/v). 1,4-butanediol (a DES component), acts as a smart cosubstrate for the enzymatic cofactor regeneration, shifting the thermodynamic equilibrium to the product side. By means of the novel DES media, cyclohexanone reduction was optimized to yield maximum productivity with low enzyme amounts (in the range of 10 g L−1 d−1). Notably, with the herein developed reaction media, cinnamaldehyde was reduced to cinnamyl alcohol, an important compound for the fragrance industry, with promising high productivities of ~75 g L−1 d−1.